In vitro activity of ceftaroline: A novel antibiotic against methicillin-resistant Staphylococcus aureus - Vaishali Gaikwad; Tejash Gohel; Shrijeet Panickar; Vijay Chincholkar; Santosh Mangalkar (Indian Journal of Pathology and Microbiology, 2016)
Introduction: Staphylococcus is one of the most common causes of nosocomial infection, especially pneumonia, surgical site infections, blood stream infections, and continues to be a major cause of community-acquired infections. The emergence of penicillin resistance followed by the development and spread of strains resistant to the semisynthetic penicillins such as methicillin, oxacillin and nafcillin, macrolides, tetracycline, and aminoglycosides has made the treatment of staphylococcal infection a global challenge. To treat this multidrug-resistant methicillin-resistant Staphylococcus aureus (MRSA), the only option available is glycopeptides such as vancomycin. However, recently, vancomycin-intermediate S. aureus and vancomycin-resistant S. aureus strains have emerged with different resistance mechanism. There are newer drugs in the pipeline against MRSA such as ceftaroline, dalbavancin, oritavancin, and tedizolid; however, very little data are available for their use. Recently, ceftaroline has been approved by the US Food and Drug Administration for the treatment of acute bacterial skin and soft tissue infections and community-acquired bacterial pneumonia due to MRSA. Hence, we tried to evaluate in vitro activity of ceftaroline against MRSA. Aim: The aim of this study was to detect in vitro activity of new cephalosporin, ceftaroline, against MRSA. Materials and Methods: Thirty nonduplicate MRSA strains were collected from various clinical samples, and minimum inhibitory concentration (MIC) was detected using ceftaroline E-test strips. Results: Twenty-eight MRSA isolates (93.33%) were found to be susceptible to ceftaroline. Conclusion: Ceftaroline demonstrated promising potency and coverage against MRSA isolates and can be considered an effective alternative treatment keeping vancomycin and linezolid as a reserved option.